Evidence of seawater drinking in fasting subadult hooded seals (Cystophora cristata) - Iraizoz, Fernando Alvira; Nordøy, Erling Sverre (Journal of Animal Behaviour and Biometeorology, 2019)
The purpose of this study was to investigate the total water turnover rate of fasting subadult hooded seals in order to elucidate to what extent these animals rely in seawater drinking/mariposia at this life stage. Considering mariposia is important for later accurate estimations of food consumption using water turnover rate as a proxy. Five subadult hooded seals were kept fasting for 4 days in a seawater pool. Total body water (39.6 ± 2.5 % of total body mass) decreased by 3.1 ± 0.4 % of initial body water over the experimental period. Turnover rates were 16.7 ± 3.9 (influx) and 24.6 ± 4.6 (efflux) ml · dayˉ¹ · kgˉ¹ with a net water loss of 710 ± 51 ml · day-1. It was estimated that the seals drank approximately 947 ml of seawater per day, which corresponds to 61 % of total daily water influx. Initial body water was relatively low as a result of the high body fat (46.9 ± 3.2 % of initial body mass) shown in the animals. It is concluded that subadult fasting hooded seals drink significant amounts of seawater during fasting. Although mariposia stands out as the major source of free water in fasting hooded seals, the amount of seawater ingested is unlikely to provide a net gain of free water as it is provided by metabolic water. However, it may contribute to excrete the excess of urea produced during early phase I of fasting.